The Faces of Torah - Hayes, Christine Elizabeth,Alexander, Elizabeth Shanks,Amit, Aaron,Appelbaum, Alan,Bakhos, Carol,Bar-Asher Siegal, Elitzur A.,Bar Asher Sigal, Mikhal,Bar-Asher Siegal, Michal,Bar-Asher, Moshe,Baumgarten, Albert I.,Berkowitz, Beth A.,Boyarin, Daniel,Bregman, Marc,Brody, Robert,Burns, Joshua Ezra,Chazon, Esther G.,Collins, John J.,Dimant, Devorah,Halberstam, Chaya,Hauptman, Judith,Hayes, Christine,Hempel, Charlotte,Himmelfarb, Martha,Hirshman, Marc,Joosten, Jan,Kalmin, Richard,Kraemer, David,Levine, Lee I. A.,Milikowsky, Chaim,Miller, Stuart S.,Noam, Vered,Novick, Tzvi,Rosen-Zvi, Ishay,Rubenstein, Jeffrey,Schremer, Adiel,Shemesh, Aharon,Stern, David,Yadin-Israel, Azzan,Yahalom, Joseph (Vandenhoeck & Ruprecht, 2017)
***Angaben zur beteiligten Person Bar-Asher Siegal: Michal Bar-Asher Siegal, PhD. is the Rosen Family Career Development Chair in Judaic Studies at The Goldstein-Goren Department of Jewish Thought at Ben-Gurion University of the Negev, Israel. ***Angaben zur beteiligten Person Baumgarten: Albert I. Baumgarten, Ph.D., is Professor em. at the Department of Jewish History at Bar-Ilan University in Ramat Gan, Israel. ***Angaben zur beteiligten Person Hayes: Christine Hayes, PhD. is Robert F. and Patricia R. Weis Professor of Religious Studies in Classical Judaica at Yale University, Connecticut. ***Angaben zur beteiligten Person Noam: Vered Noam, Ph.D., ist Privatdozentin an der Fakultät für Hebräische Kulturwissenschaft der Universität Tel-Aviv. ***Angaben zur beteiligten Person Novick: Tzvi Novick, PhD. holds the Abrams Chair of Jewish Thought and Culture in the Department of Theology at the University of Notre Dame, Indiana. This volume is a festschrift in honor of Steven Fraade, the Mark Taper Professor of the History of Judaism at Yale University. The contributions to the volume, written by colleagues and former students of Professor Fraade, reflect many of his scholarly interests. The scholarly credentials of the contributors are exceedingly high. The volume is divided into three sections, one on Second Temple literature and its afterlife, a second on rabbinic literature and rabbinic history, and a third on prayer and the ancient synagogue.Contributors are Alan Applebaum, Joshua Burns , Elizabeth Shanks Alexander , Chaya Halberstam , John J. Collins, Marc Bregman, Aharon Shemesh, Ishay Rosen-Zvi, Vered Noam, Robert Brody, Albert Baumgarten, Marc Hirshman, Moshe Bar-Asher, Aaron Amit, Yose Yahalom, Lee Levine, Jan Joosten, Daniel Boyarin, Charlotte Hempel, David Stern, Beth Berkowitz, Azzan Yadin, Joshua Levinson, Elitzur Bar-Asher Siegal, Michal Bar-Asher Siegal, Tzvi Novick, Devora Diamant, Richard Kalmin, Carol Bakhos, Judith Hauptman, Jeff Rubenstein, Martha Himmelfarb, Stuart Miller, Esther Chazon, James Kugel, Chaim Milikowsky, Maren Niehoff, Peter Schaefer, and Adiel Schremer.
10.13109/9783666552540
Keywords: Festschrift; Aufsatzsammlung; Fraade; Steven D.; Frühjudentum; Rabbinische Literatur; Literatur